(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article examines the role and importance of social life in the development of the creative activity of Primary School students, and methods for the formation of creative activity through thinking and imagination. In addition to this, the first manifestations of creativity in primary school students were studied during the non-productive periods.